Prehospital cardiac arrest resuscitation practices differ around the globe - Kjær, Jeannett (2025)
Background: Out-of-hospital cardiac arrest (OHCA) is a major public health problem. This study aims to describe the international variations in the practices related to the initiation, termination, and refraining from resuscitation of adult patients (≥18 years) with a non-traumatic OHCA. Methods: An exploratory descriptive study was conducted using a cross-sectional online survey. The respondents were recruited using snowball sampling technique. Framework analysis was used to identify key themes in responses, with descriptive statistics summarising data trends. Results: The study collected responses from 59 countries. Our findings reveal that respondents from 59.3% of countries reported that they initiate resuscitation in all cases where the patients do not show obvious signs of irreversible death or do not have confirmed advance directives. Respondents from 15.3% of countries reported that once started, prehospital resuscitation attempts are not terminated. Prehospitally respondents from 20.3% of the countries reported that they rely exclusively on specific criteria to decide when to terminate resuscitation efforts while in 45.8%, these decisions are made at the discretion of the provider. Respondents from most countries (91.5%) reported that they refrain from resuscitation in the presence of obvious signs of irreversible death. Respondents from 57.6% of countries, reported that they refrained from resuscitation if the patient had a confirmed do-not-attempt-cardiopulmonaryresuscitation (DNACPR), while 15.3% mentioned staff safety as a reason to abstain from attempting resuscitation. Conclusion: This study reveals global variation in EMS resuscitation practices, reflecting disparities in resources, healthcare infrastructure, EMS system design, community acceptability given cultural and societal norms, and legislation.